2011
DOI: 10.1161/hypertensionaha.111.176701
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of Bcl-2 During the Senescence Exacerbates the Impaired Angiogenic Functions in Endothelial Cells by Deteriorating the Mitochondrial Redox State

Abstract: Abstract-Ageing is an important risk factor for ischemic cardiovascular diseases, although its underlying molecular mechanisms remain to be elucidated. Here, we report a crucial role of Bcl-2 in the impaired angiogenic functions in senescent endothelial cells (ECs) by modulating the mitochondrial redox state. Cellular senescence impaired angiogenic functions in ECs without attenuating the mitogen-activated protein kinase or Akt signaling, and vascular endothelial growth factor receptor 2 or Tie-2 expressions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
(25 reference statements)
3
23
0
Order By: Relevance
“…So, these results raised a new issue to further study the molecular mechanisms involve in modulatory activity of miR-15b on VEGF and Ang2 expression. Further, BCL2 is not a mediator in the angiogenic process of BP classification in GO; however, many studies suggested its functional role in promoting angiogenesis [52,53]. In our results, BCL2 gene is potentially suppressed by miR-15b through bioinformatic prediction.…”
Section: Discussionmentioning
confidence: 50%
“…So, these results raised a new issue to further study the molecular mechanisms involve in modulatory activity of miR-15b on VEGF and Ang2 expression. Further, BCL2 is not a mediator in the angiogenic process of BP classification in GO; however, many studies suggested its functional role in promoting angiogenesis [52,53]. In our results, BCL2 gene is potentially suppressed by miR-15b through bioinformatic prediction.…”
Section: Discussionmentioning
confidence: 50%
“…Increased mitochondrial oxidative stress has been shown to impair angiogenic functions (90) and promote apoptosis in endothelial cells. We tested the hypothesis that the marked anti-oxidative action of CR is associated with pro-angiogenic and anti-apoptotic endothelial effects.…”
Section: Cr Attenuates Age-related Oxidative Stress In Aged Cmvecsmentioning
confidence: 99%
“…1 In aged animals and elderly human subjects, the arterial endothelium exhibits morphological features of cellular senescence: flat and enlarged multinuclear endothelial cells that show positive staining of senescence-associated ␤-galactosidase (SA-␤-gal). [2][3][4][5][6] Cellular senescence correlates with aging-induced endothelial dysfunction and decreased production of endotheliumderived vasodilators such as nitric oxide and prostacyclin. [7][8][9] Moreover, senescent endothelial cells are proinflammatory and proatherosclerotic and have a decreased regenerative capacity.…”
mentioning
confidence: 99%